Using Cognitive Behavioral Strategy to Overcome Affective Factors of Students' Speaking in Senior High School - Rizqy, Elmira (RETAIN : Journal of Research in English Language Teaching, 2022)
The aim of this study is to investigate the student speaking problemand the effect of student speaking factor trough behavioral strategy. This research used quantitative research design. This research used questionnaires and observation as instruments to gain the data. The subjects of this study are 21 students in senior high school. The data would be analyzed in quantitative-descriptive. It was found that by using cognitive behavioral strategy, students could make improvement only on affective factors while for listening ability, topical knowledge and performance condition, there is no impact at all.